Sintesis 4-Hidroksisinamamida dari Asam 4-Hidroksinanamat melalui Reaksi Esterifikasi dan Amonolisis - Firdaus Firdaus; Nunuk Hariani Soekamto; Abdul Karim (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2009)
The 4-hydroxycinnamamide  is a compound  that has been isolated from the root bark of Kleinhovia hospita Linn. The compound show high toxicity to Artemia salina Leach (IC 180,53 µg) so it can be expected has cytostatic activity against P388 leukemic cells. However, the concentration of the compound in the root bark of K. hospita Linn is very low (about 1.6 ppm), and commercially the compound  is  not  ready  and  has  never  been  synthesized.  Therefore,  it  is  important  to  find  out  a synthesis method to used in prepare the compound for further examination, in particular its cytostatic activity. By this research, the 4-hydroxycinnamamide compound has been prepared from 4- hydroxycinnamic  acid  via  esterification  reaction  with  excess  ethanol  and  sulphate  acid  catalyst followed  ammonolysis  reaction  with concentrated  ammonia.  The esterification  stage  gave  ethyl 4-hidroxycinnamate   as  white  crystall  with  melting  point  133-134oC   and  34.9%  yield,  and  the ammonolysis stage gave 4-hydroxycinnamamide as white crystall with merting point 140oC and 46.1% yield. Identification of the reaction product was carried out by FTIR and NMR spectroscopy methods.Keywords: 4-hydroxycinnamamide, 4-hydroxycinnamic acid, esterification, ammonolysis